Optimization of Convective Tray-Drying Process Parameters for Green Banana Slices Using Response Surface Methodology and Its Characterization - Meenatai Kamble; Anurag Singh; Sukh Veer Singh; Ajay Chinchkar; Sunil Pareek (Journal of Food Quality)
Green banana (Musa spp.) is a significant source of starch (resistant starch ∼50%), phenolics and flavonoid compounds, and minerals (K, Mg, Zn, and Fe). The utilization of green bananas in their fresh form is limited, whereas the drying of bananas provides the opportunity to use them for various purposes. Drying temperature and slice thickness are important to be optimized for drying of bananas as they affect the quality parameters. The present study was conducted using response surface methodology to optimize tray-drying temperatures (50–80°C) and slice thicknesses (2–8 mm) on the basis of phytochemical and physical parameters of dried green banana slices. The cubic model was found to be the best fit for most of the responses (R2 = 0.95–1), and the quadratic model was fit for water activity (aw) (R2 = 0.92). The optimized drying conditions were found as drying temperature of 50°C and slice thickness of 4.5 mm. Experimental responses exhibited maximum L∗ (84.06), C∗ (13.73), and ho(83.53) and minimum losses of total phenolic content (89.22 mg GAE/100 g) and total flavonoid content (3.10 mg QE/100 g) along with lower aw (0.25). The optimized green banana flour was rich in carbohydrates (77.25 ± 0.06%) and low in fat (1.79 ± 0.11%). The flour obtained had good flowability with a mean particle size of 60.75 ± 1.99 µm. Flour’s gelatinization and decomposition temperatures were 102.7 and 292°C, respectively. In addition, flour’s water absorption, oil absorption, and solubility were 5.19 ± 0.01, 1.58 ± 0.01, and 0.14 ± 0.02 g/g, respectively. Green bananas dried at optimized conditions resulted in a better product with less phytochemical loss than dried with other methods.